Upaya Meningkatkan Minat dan Hasil Belajar IPA melalui Pembelajaran Inkuiri Terbimbing (PIT) pada Peserta Didik Kelas VIII Di SMP Negeri 1 Kebumen - Badyani Badyani (LPPM Institut Agam Islam Nahdlatul Ulama (IAINU) Kebumen, 2022)
This study aims to determine the application of the PIT (Guided Inquiry Learning) model in increasing the interest and results of learning science in class VIII students of SMP Negeri 1 Kebumen. This research is a classroom action research (CAR) using three cycles. Each cycle consists of 2 meetings. The subjects of this study were students in class VIII-A, which consisted of 30 students. Data collection techniques include observation, interviews, tests, and documentation. Data analysis techniques use the Miles and Huberman model. Based on the results of the study it can be concluded: The PIT (Guided Inquiry Learning) model can increase students' interest and learning outcomes in science subjects in class VIII. This can be seen from the increase in the average score of interest in learning science class VIII-A SMP Negeri 1 Kebumen, namely in the initial conditions of 76.57, in cycle I of 82.53, in cycle II of 89.43 and in cycle III of 99.23. While the increase in learning outcomes can be seen from the increase in the average student learning outcomes, namely the value in the initial conditions of 69.58, in the first cycle of 82.78, in the second cycle of 85.83, and in the third cycle of 91.67. The percentage increase in the learning outcomes of students who achieved grades above the KBM = 80 in the initial conditions was 20%, in the first cycle it was 66.67%, in the second cycle it was 83.33% and in the third cycle it reached 100%.